Gestural tendencies in composing pieces for solo clarinet in sequenza ix for clarinet, garisan, and klibat - Salleh, Marzelan; Mohamed Razali, Camellia Siti Maya (Universidade Federal de Goias, 2023)
Abstract: Gesture in a broader sense is more than a physical movement but, can also be modes of expression representing specific meanings. Movements with meaning embodies gesture and gesture exists in various artforms like music because of its capacity to express. Its capability to transform through time and space makes it akin to energy and it is parallel with the art of composing music. Musical gesture however, are being studied at different levels so as to classify and to relate different functions of gestures. This article intends to demonstrate the use of musical gestures into composing music for a solo wind instrument. Three solo pieces for clarinet were written by three different composers approaching musical composition through gestural writing. To realize the imagined sound and movements of the clarinet, the composers’ composing process concentrated more on the gestural movements and tone colours of the selected wind instrument. The musical gesture in these three solo pieces is actually capturing the movement and sense of movement through music, and its essence lies in the subconscious lines connected to create direction and motion in both pieces. This compositional approach also gives the composers more compositional freedom and enriches their compositional process. Keywords: music composition, musical gesture, solo pieces for clarinet, contemporary music.